Keamanan Susu Fermentasi Yang Beredar Di Banda Aceh Berdasarkan Nilai Gizi dan Jumlah Bakteri Pathogen - Yusdar Zakaria; Cut Intan Novita; Mira Delima (Agricultural Faculty, 2010)
Safety condition of commercial fermented milk that put on the market in banda aceh based on nutritive value and pathogenic bacteriaABSTRACT. Fermented milk has much value primarily for the health of digestive system. However without hygienically and sterilized treatment it can become toxic to consumers. This research was conducted to observe nutritive value, the present of pathogenic bacteria, and the safety condition of commercial fermented milk that put on the market in Banda Aceh. Samples of commercial fermented milk tested were obtained from recognized retailers in Banda Aceh. Factorial completely randomized design with six replications was applied in this research. Variety of fermented milk products (yoghurt and drink yoghurt) was the first factor to be analyzed, and the second one was expired date of the products (the date of production and the date of by expired). The amount of crude protein and lipid, pH level, and the amount of lactic acid bacteria, Coliform and Staphilococcus aureus were the parameter determined. The variety and the expired date of the products influenced the amount of crude protein and lipid, the pH level, the amount of lactic acid bacteria, Coliform and Staphilococcus aureus in the level of highly significant different (P0,01). There was also found in highly significant interaction (P0,01) between factors that influenced the amount of lactic acid bacteria and Staphilococcus aureus. On the other hand, the amount of Coliform was not influenced by those factors. The study also results in decreasing of the amount of crude protein and lipid as well as lactic acid bacteria caused by the ongoing time of storing. The longer fermented milk was stored, the lower the level of crude protein, lipid and lactic acid bacteria presented. The lipid level of fermented milk products those put on the market in Banda Aceh have been complied with the requirement standard of SNI 01-2981-1992. However, crude protein level has not achieved the requirement standard yet. Due to the amount of Staphylococcus aureus present, the fermented milk products tested, in fact, were not saved to be consumed. On the contrary, although Coliform was also present, the products were in the category of saved to be consumed.